A statistical study on structures of patient privacy in Iran and their violations - Ehsan Kazemnejad Leyli; Morteza Rahbar Taremsari; Hamid Mohammadi Kojidi; Mahsa Faramin Lashkarian (Journal of Hyperstructures, 2024)
The aim of all the studies that have been conducted on the concept of patient privacy is to improve the standards of care. Personal privacy is a basic human principle and as a fundamental right of every human being, it is an important and necessary requirement that must be observed in health care and nursing organizations. Due to the fear of emerging and contagious diseases and the patients' fear of rejection from their families and in a wider sense of society, they hesitate to express the symptoms of contagious diseases as a social stigma, and this issue itself leads to disruption in It becomes the treatment process of the patients and doubles the importance of preserving the privacy of the patients. \linebreak Considering the many and abnormal consequences of violating the patient's privacy, such as increasing anxiety, stress, inciting aggressive and violent behaviors, and more importantly, hiding parts of the patient's history or medical history due to the concern of violating their privacy. This research will be conducted with the aim of investigating the level of privacy compliance and its related factors in corona patients of Razi Hospital in Rasht city in 2022.